Traitement contrastif des sequences figees (SF) et probleme de leur equivalence interlinguale - Sułkowska, Monika (Neophilologica, 2004)
The aim of the article is to discuss some issues concerning the problem of interlinguistic equivalence of phraseologisms. The article presents the assumptions and objectives of comparative phraseology. The author shows different aspects of equivalence.